INTEGRITAS LAPORAN KEUANGAN DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Endah Ayu Dewanti; Arwina Karmudiandri (E-Jurnal Akuntansi TSM, 2023)
This study aims to determine the effect of institutional ownership, managerial ownership, audit committee, company size, leverage, financial distress, profitability and investment opportunity set on the integrity of financial statements in non-financial companies that are consistently listed on the Indonesia Stock Exchange (IDX) with the period from 2019 to 2021. The number of samples in this study were 148 companies with a research period of 3 years, so that the total sample obtained for this study was 444 company data. The method used for research sampling is purposive sampling method. While the analytical method of this study uses multiple linear regression analysis techniques to test hypotheses with IBM SPSS Statistics 25. The results of the study show that institutional ownership, leverage, profitability and investment opportunity set have a positive effect on the integrity of financial statements. Then financial distress has a negative effect on the integrity of financial statements. Meanwhile managerial ownership, audit committee and company size have no effect on the integrity of financial statements.